Habitat heterogeneity and use of physical and acoustic space in anuran communities in Southeastern Brazil - Da Silveira Vasconcelos, Tiago [UNESP]; De Cerqueira Rossa-Feres, Denise [UNESP] (My University, 2008)
Habitat heterogeneity and use of physical and acoustic space in anuran communities in Southeastern Brazil. We intended to verify if structural and physiognomical characteristics of water bodies influence on the degree of overlap among calling sites of 23 anurans species, if anuran species use different calling sites in different water bodies, and if there is some relationship between the degree of advertisement call (based on seven call features) and calling site differentiation. Then, we determined calling sites (based in four variables) and recorded the advertisement call for anuran species that occurred in 10 water bodies of northwestern São Paulo State. We also determined the environmental heterogeneity (based in four environmental descriptors) for each water body. Males of most species used similar calling sites in each water body, probably because of the high uniformity of the environment, as a consequence of agricultural impacts on edge vegetation of the studied ponds. Most species (18 out of 19 species) called from different sites in the ponds where they occurred, which can be associated with differences in horizontal and vertical distribution of vegetation in the studied ponds. From the 19 species analyzed, only males of Pseudopaludicola aff. saltica called in sites with the same characteristics in different ponds. Advertisement call of Hylidae species was more similar to each other than were Leiuperidae and Leptodactylidae among themselves. The aquatic/terrestrial anurans (Bufonidae, Leiuperidae, Leptodactylidae and Microhylidae) occupied similar calling sites but presented quite distinct advertisement calls, while Hylidae species presented an inverse pattern: a high similarity on advertisement call features but used different calling sites, which indicates a niche complementarity between physical (calling site use) and acoustic (advertisement call) space use. © 2008 Departamento de Ciências Biológicas.
Keywords: Advertisement call; Anura; Calling site; Environmental heterogeneity; Microspatial distribution; calling behavior; frog; geographical distribution; heterogeneity; pond; space use; Brazil; Sao Paulo [Brazil]; South America; Bufonidae; Hylidae; Leptodactylidae; Microhylidae; Pseudopaludicola